2015
DOI: 10.1007/s10964-015-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Basic Psychological Need Satisfaction, Emotion Dysregulation, and Non-suicidal Self-Injury Engagement in Young Adults: An Application of Self-Determination Theory

Abstract: Non-suicidal self-injury (NSSI) is a public health concern that affects young adults at alarming rates. The present study examines the role of satisfaction of self-determination theory's three basic needs for autonomy, competence, and relatedness in young adults' NSSI engagement. University students who reported ever having engaged in NSSI (n = 40, 85 % female; Mage = 20.10, SD = 1.66) reported significantly lower levels of the satisfaction of all three needs, as well as more difficulties with all aspects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 52 publications
0
34
0
1
Order By: Relevance
“…To further examine the role of emotional regulation in first‐episode D‐SIB, we carried out regression analyses on the dimensions of the difficulties in the emotional regulation scale (Gratz & Roemer, ). Previous research from inpatient and older adolescent postinjury populations suggests that prospective self‐harm is most associated with the limited access to strategies component of DERS (Emery et al., ; Gratz & Roemer, ; Perez et al., ). We did not find such an association with first‐episode D‐SIB; in fact, our findings revealed that, prior to D‐SIB, lack of emotional clarity was the only emotional difficulty significantly associated with the development of initial D‐SIB while controlling for anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…To further examine the role of emotional regulation in first‐episode D‐SIB, we carried out regression analyses on the dimensions of the difficulties in the emotional regulation scale (Gratz & Roemer, ). Previous research from inpatient and older adolescent postinjury populations suggests that prospective self‐harm is most associated with the limited access to strategies component of DERS (Emery et al., ; Gratz & Roemer, ; Perez et al., ). We did not find such an association with first‐episode D‐SIB; in fact, our findings revealed that, prior to D‐SIB, lack of emotional clarity was the only emotional difficulty significantly associated with the development of initial D‐SIB while controlling for anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that the link between emotional dysregulation and NSSI was robust across participants from various countries, such as the United States [42,51], Canada [59][60][61], Italy [52], Germany [55][56], New Zealand [62][63], and the Netherland [57], these countries are all western countries and participants in these studies were predominantly identified as Caucasian. Only two studies being reviewed involved non-western samples: one involved Turkish [38], and the other Japanese [64].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Because of their overpowering nature, emotions can be expressed in unmodulated or impulsive ways, or alternatively they may be withheld. Emotion dysregulation is then associated not only with greater subjective distress and self-harming behavior (e.g., Emery, Heath, & Mills, 2016) but also with greater peer rejection, often because of expressive outbursts, disruptions, or withdrawal (e.g., Shields, Cicchetti, & Ryan, 1994). Regardless of expressing or withholding emotions, when dysregulated the individual experiences little choice in behavior, with accompanying relational tensions and subjective ill-being (Roth & Assor, 2012; Roth et al, 2009).…”
Section: Sdt's Taxonomy Of Emotion Regulation Stylesmentioning
confidence: 99%